Previous active cognitive task does not affect subsequent self-paced exercise in the heat - Roussey, G.; Gruet, M.; Vercruyssen, F.; Bernard, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Prolonged periods of strenuous cognitive activity has recently been demonstrated to negatively influence the selfregulated physical tasks and is likely to compromise endurance performance (Brownsberger et al., 2013). In this framework, no studies have yet investigated whether or not hot ambient conditions modified the previously observed production of less power during hard effort bout. The aim of this study was to compare impact of two different (active vs passive) cognitive tasks preceding a hard self-paced exercise in temperate and hot ambient conditions on power output, thermal state and thermal comfort perceived. METHODS: In a randomized cross-over design, ten well-trained male cyclists completed four 30-min cycling trials at self-selected intensity representative of hard effort (RPE15-Hard), either in temperate (TMP, 20°C) or in hot conditions (HOT, 35°C). Before exercise, participants completed during 60 min either a Stroop-incongruent activity task or a time-matched passive task (control). Physiological, psychological indices were assessed throughout the four trials. RESULTS: Pre-exercise tasks induced similar subjective feelings of fatigue in spite of higher mental workload induced by cognitive activity task (p<0.05). No effect on power and any other assessed variable during the cycling trial has been observed in both ambient conditions. Mean power was significantly lower in HOT than in TMP (64.8±4.0 vs 70.7±5.0 %PMA respectively, p<0.001) but pacing design were not be affected. Average values of skin temperature (p<0.001) and thermal sensation (p<0.001) were significantly higher in HOT whereas heart rate and central temperature were similar. DISCUSSION: The present study, using an original model of self-paced exercise (Tucker et al. 2006), shows strong links between mean power, higher skin temperature and thermal sensation in the heat. These findings support that perceived exertion plays a key role in self-selected work rate during exercise in the heat through behavior thermal feelings (Schlader et al. 2011). Similar levels of mental fatigue reached the previous two cognitive tasks could explain the lack of difference in perception of effort.